2019
DOI: 10.1038/s41419-019-2178-9
|View full text |Cite
|
Sign up to set email alerts
|

G3BP1 inhibits RNA virus replication by positively regulating RIG-I-mediated cellular antiviral response

Abstract: Retinoic acid-inducible gene I (RIG-I) is a pattern recognition receptor and is involved in the innate immune response against RNA viruses infection. Here, we demonstrate that the Ras-GTPase-activating protein SH3-domain-binding protein 1 (G3BP1) serves as a positive regulator of the RIG-I-mediated signaling pathway. G3BP1-deficient cells inhibited RNA virus-triggered induction of downstream antiviral genes. Furthermore, we found that G3BP1 inhibited the replication of Sendai virus and vesicular stomatitis vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 40 publications
(42 reference statements)
2
79
0
Order By: Relevance
“…We also found that Orf9b interacts with a mitochondrial import receptor, Tom70, which acts as an essential adaptor linking MAVS to TBK1/IRF3, resulting in the activation of IRF-3 51 . N targets stress granule protein G3BP1, an essential antiviral protein which is known to induce innate immune response through multiple mechanisms [52][53][54] . Common among coronaviridae is the manipulation of stress granules (SG) and related RNA biology, possibly leading to suppression of stress granules and host translation shutoff 55 .…”
Section: Sars-cov-2 Interacts With Multiple Innate Immune Pathwaysmentioning
confidence: 99%
“…We also found that Orf9b interacts with a mitochondrial import receptor, Tom70, which acts as an essential adaptor linking MAVS to TBK1/IRF3, resulting in the activation of IRF-3 51 . N targets stress granule protein G3BP1, an essential antiviral protein which is known to induce innate immune response through multiple mechanisms [52][53][54] . Common among coronaviridae is the manipulation of stress granules (SG) and related RNA biology, possibly leading to suppression of stress granules and host translation shutoff 55 .…”
Section: Sars-cov-2 Interacts With Multiple Innate Immune Pathwaysmentioning
confidence: 99%
“…Overexpression of G3BP1 was shown to induce the formation of SGs to which innate immune factors such as PKR, oligoadenylate synthetase (OAS) 2, and RNase L are recruited, which, in turn, promote the production of certain cytokines such as IL-17, MIP-3a/b, and MCP-5 via activation of the NF-κB and JNK pathways [256]. Independently of its role in SG assembly, G3BP1 was also shown to interact with the RNA sensor RIG-I and positively regulates its downstream signaling [306,307], as well as with the DNA sensor cGAS, thereby enhancing IFN-β production [308]. This might be the reason why several members of the Picornaviridae and related viruses have evolved G3BP1-cleaving proteases, as reported for the Leader protein of foot-and-mouth disease virus, Theiler's murine encephalomyelitis virus (TMEV) and mengovirus [280,309,310], the proteinase 3C of poliovirus, coxsackievirus B3 and encephalomyocarditis virus (EMCV) [245,[311][312][313], as well as the 3C-like proteinase NS6 of feline calicivirus [314].…”
Section: G3bp1 At the Interface Between Sgs And The Ifn Responsementioning
confidence: 99%
“…Activation of RNase L by 2-5A produces dsRNA intermediates that signal through Rig-I and or MDA5 via mitochondrial adaptor, MAVS (IPS-1) by activating IRF3 that translocates to the nucleus to enhance IFN-β production (46). Various studies have shown that G3BP1 binds to Rig-I to regulate IFN-β production in response to viral RNA and synthetic dsRNA, polyI:C (39, 52, 53). To examine whether G3BP1 participates in RNase L-mediated IFN-β production, we monitored IFN-β promoter activation in WT and G3BP1 KO cells by directly activating RNase L with 2-5A or introducing RNase L-cleaved small RNAs and compared to control small RNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced levels of IFN-β production facilitated higher replication of SeV in both RNase L KO and G3BP1 KO cells with loss of antiviral effect. A recent study suggests that G3BP1 inhibits SeV and VSV replication by suppressing RNF125-mediated ubiquitination of Rig-I resulting in increased Rig-I expression and IFN production (53). These observations suggest that G3BP1 may regulate host response to viral infections at multiple levels by regulating activity of PRRs like Rig-I as well as nucleating avSG formation.…”
Section: Discussionmentioning
confidence: 99%